Basic Training Of Child Pharmacists At SDN 1 Sesaot In The Use Of Appropriate Drugs Early On In West Lombok - Riska Wahyuningsih; Laeli Fitriyati; Isma Yuniar (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Training is the systematic process of changing one's behavior in a direction to improve one's knowledge and skills. Little pharmacist or commonly abbreviated as Apocil is a social agenda that is a real action to educate the public, especially children in terms of introduction to pharmacy. Drugs are all single ingredients or mixtures that are used by all beings to the inside and outside , in order to prevent , alleviate , and cure diseases. The purpose of the implementation of this activity is to introduce the profession of pharmacist is part of health workers in the community. the results of 85% of the students know and understand about the pharmacist young and Remedies of a matter that is given before and after the exposure of the material that is given.